EFEKTIVITAS EDUKASI MULTIMEDIA DALAM MENINGKATKAN PENGETAHUAN, SIKAP, DAN PERILAKU REMAJA DALAM PENCEGAHAN DIABETES MELLITUS: EFFECTIVENESS OF MULTIMEDIA EDUCATION IN IMPROVING ADOLESCENTS’ KNOWLEDGE, ATTITUDES, AND BEHAVIORS IN DIABETES MELLITUS PREVENTION - Wartonah Wartonah; Santa Manurung; Tarwoto Tarwoto; Tri Endah Pangastuti; Nurhalimah Nurhalimah; Yulia Ratna Dewi (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Diabetes Mellitus is one of the non-communicable diseases with an increasing prevalence, including among adolescents. This condition highlights the importance of promotive and preventive efforts through health education that is appropriate to adolescent characteristics. This study aimed to analyze the effectiveness of multimedia-based education in improving adolescents’ knowledge, attitudes, and behaviors related to Diabetes Mellitus prevention. This study employed a quasi-experimental design using a pre-test and post-test with control group approach. A total of 60 respondents were recruited and divided into an intervention group (n=30) and a control group (n=30) using a simple random sampling technique. The intervention group received health education through a ±10-minute educational video delivered twice during a two-week intervention period, while the control group received standard education in the form of health leaflets. The research instrument consisted of questionnaires assessing knowledge, attitudes, and behaviors regarding Diabetes Mellitus prevention. Data were analyzed using paired t-test and independent t-test with a significance level of p<0.05. The results showed significant improvements in the intervention group in terms of knowledge (p=0.009), attitudes (p=0.002), and behaviors (p=0.003) compared to the control group, with moderate effect sizes on knowledge (d=0.42), attitudes (d=0.61), and behaviors (d=0.48). Multimedia-based education using video media was found to be effective in improving adolescents’ understanding, promoting positive attitudes, and encouraging preventive behaviors toward Diabetes Mellitus prevention. These findings may serve as a basis for developing digital-based health education programs in schools as part of early prevention strategies for non-communicable diseases.